Effect of environmental parameters on pathogen and faecal indicator organism concentrations within an urban estuary. (5th June 2016) - Henry, Rebekah; Schang, Christelle; Kolotelo, Peter; Coleman, Rhys; Rooney, Graham; Schmidt, Jonathan; Deletic, Ana; McCarthy, David T.
Abstract: Current World Health Organisation figures estimate that ∼2.5 million deaths per year result from recreational contact with contaminated water sources. Concerns about quantitative risk assessments of waterways using faecal indicator organisms (FIOs) as surrogates to infer pathogenic risk currently exist. In Melbourne, Australia, the Yarra River has come under public scrutiny due to perceived public health risks associated with aquatic recreation; a characteristic shared with urban estuaries worldwide. A 10-month study of the Yarra estuary investigated the processes that affect FIOs and pathogens within this system. A total of 74 samples were collected from three estuarine and two upstream, freshwater, locations under different climatic and hydrological conditions, and the levels of Escherichia coli, enterococci, Clostridium perfringens, fRNA coliphages, Campylobacter spp. Cryptosporidium oocysts, Giardia cysts, adenoviruses, and enteroviruses were monitored. Reference pathogenic bacteria, protozoa, and viruses were detected in 81%, 19%, and 8% of samples, respectively. Variations in FIO concentrations were found to be associated with changes in specific climatic and hydrological variables including: temperature, flow, humidity and rainfall. In contrast, pathogen levels remained unaffected by all variables investigated. Limitations of current national and international culture-based standard methods may have played a significant role in limiting the identification of correlative relationships The data demonstrate the differences between FIOs and microbial pathogens in terms of sources, sinks, and survival processes within an urban estuary and provide further evidence of the inadequacy of FIO inclusion in the development of worldwide regulatory water quality criteria and risk assessment models.